SGLT2 Inhibitors, GLP-1 Agonists, and DPP-4 Inhibitors in Diabetes and Microvascular Complications: A Review. (29th February 2020) - El Mouhayyar, Christopher; Riachy, Ruba; Khalil, Abir Bou; Eid, Asaad; Azar, Sami
Abstract : The prevalence of diabetes and its associated complications is increasing throughout the decades. Promising diabetes medications were introduced to the market including GLP-1 agonists, DPP-4 inhibitors, and SGLT2 inhibitors aiming to target these complications. The literature lacks sufficient data regarding these new medications and their influence on nephropathy, retinopathy, and neuropathy. This review expands on the major results of effects of the 3 drug classes on microvascular complications. In our review, both SGLT2 inhibitors and GLP-1 agonists appear to have promising nephroprotective outcomes at this stage, with less promising outcomes seen with DPP-4 inhibitors. Moreover, the retinoprotective outcomes of both SGLT2 inhibitors and DPP-4 inhibitors were only tested on mice, while those of GLP-1 agonists were assessed in few trials. In addition, the results of both GLP-1 agonists and DPP-4 inhibitors showed discrepancies in these studies. On the contrary, conclusions regarding the effect of these medications on neuroprotective outcomes cannot be drawn at the time due to the lack of clinical trials targeting these complications. Hence, a clearer picture of the microvascular outcomes will manifest over time with the release of multiple upcoming clinical trials.